Women’s Empowerment in India-South Korea Relations: A Shared Journey - Subhash Kumar Baitha; Rinkal Tyagi; Kumar Rajak, Sumit (The Indonesian Journal of Social Studies, 2023)
One thread, the common dedication to women’s empowerment, shines out clearly in the complex tapestry of India-South Korea ties. The essay highlights the advancements achieved by both countries in advancing women’s rights, education, and workforce involvement as it examines the changing landscape of gender equality programmes. Governments have passed laws to remove gender barriers, creating an atmosphere where women may succeed both personally and professionally, from Seoul to New Delhi. We explore into the transforming impact of cross-cultural interactions, such Bollywood and K-dramas, on social perspectives and women’s empowerment. We look at programmes and possibilities in school that provide South Korean and Indian women the information and abilities they need to succeed in a variety of disciplines, including STEM. We also discuss issues like gender-based violence and job discrimination that affect women in both nations, as well as joint initiatives aimed at addressing these obstacles. Inspiring women who have achieved success in their various communities and established themselves as role models for others are also highlighted in this article. Together, India and South Korea are paving the way for a more accepting and fairer world for women, reiterating the notion that it is not just a local issue but also a shared journey that is deepening the ties between their two countries.